Gloger's Rule or Historical Conjecture? Tests in Mammals - Natasha Howell; Tim Caro (Ecology and Evolution)
ABSTRACT Gloger's rule states that homeotherms are darker at lower latitudes; however, a number of 19th‐century naturalists also suggested that animals are more brightly coloured in the tropics than in temperate regions. Using phylogenetic comparative methods, we investigated and compared both ideas across a global sample of 2726 species of mammals, examining their head, torso, legs and tail regions. Coloration data were obtained from photographs and compared with a colour chart specifically devised for mammals; ecological data were extracted from pre‐existing, open‐source databases. All analyses were conducted using phylogenetic comparative generalised linear mixed models in a Bayesian framework. We found strong support for mammals being darker in the tropics and in areas of high precipitation and evapotranspiration, little support for them being darker in warmer areas, little support for them being redder in more arid regions (a more nuanced interpretation of Gloger's rule), and virtually no support for 19th‐century naturalists' conjecture regarding coloration, contrast, or patterning being more conspicuous in the tropics. These results were replicated at both class and order levels. Our findings provide clear evidence for eumelanic coloration to be more prevalent in more humid climates (one facet of Gloger's rule), operating at a class level, but indicate that 19th‐century observations about bright coloration in the tropics do not pertain to mammals. Our results confirm the importance of Gloger's rule across mammals as a whole and add to a growing tide that darker coloration is linked to humidity at a macroecological scale.